RETRACTED: Literatur Review: Coronavirus Disease 2019 (Covid-19) Pada Kehamilan - Purnamasari, Kurniati Devi; Ningrum, Widya Maya; Fatimah, Siti; Heryani, Sri (Wellness And Healthy Magazine, 2022)
Retraction Notice Following a rigorous, carefully concerned and considered review of the article published in the Wellness and Healthy Magazine to an article entitled “Literatur Review: Coronavirus Disease 2019 (Covid-19) Pada Kehamilan” Vol 4, No 1, pp. 19–30, February 2022, DOI: http://doi.org/10.30604/well.184412022This paper has been found to be in violation of the Wellness and Healthy Magazine Publication principles and has been retracted (please seehttps://wellness.journalpress.id/wellness/about/editorialPolicies#custom-1).The article contained redundant material, the editor investigated and found that the paper was published in the Journal of Health Science and Physiotherapy, 4(1), 1-8. https://doi.org/10.35893/jhsp.v4i1.79, entitled "Literatur Review: Coronavirus Disease 2019 (Covid-19) Pada Kehamilan".http://jurnal.stikes-sitihajar.ac.id/index.php/jhsp/article/view/79The document and its content have been removed from the Wellness and Healthy Magazine, and a reasonable effort should be made to remove all references to this article.